2008
DOI: 10.1590/s1519-69842008000400024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food restriction on the reproduction and larval performance of matrinxã, Brycon amazonicus (Spix and Agassiz, 1829)

Abstract: This work evaluated the effect of food restriction and refeeding of matrinxã females, Brycon amazonicus, on their reproductive performance and on the growth and survival of the progeny. Broodstocks were distributed in 8 earthen tanks (15 fish/tank) and fish from 4 tanks were fed daily (G1) while fish from the other 4 tanks were fed for 3 days and not fed for 2 days (G2) during 6 months prior to artificial spawning. Among the induced females, 57% in G1 group and 45% in G2 group spawned and the mean egg weights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…Phenotypic convergence in offspring that differ in initial size due to maternal effects has been attributed to compensatory growth in various taxa (e.g. Wilson & Réale 2006; Reitzel & Heyland 2007; Camargo & Urbinati 2008). Although minor in comparison with food ratio, we found a strikingly long lasting effect of egg size on fish length and body mass (12 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic convergence in offspring that differ in initial size due to maternal effects has been attributed to compensatory growth in various taxa (e.g. Wilson & Réale 2006; Reitzel & Heyland 2007; Camargo & Urbinati 2008). Although minor in comparison with food ratio, we found a strikingly long lasting effect of egg size on fish length and body mass (12 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Often the mechanism behind an observed fitness effect of egg size is not identified, which is possibly due to the fact that individuals are usually not individually tracked from the egg stage (e.g. Camargo & Urbinati 2008; Donelson, Munday & McCormick 2009; Dziminski, Vercoe & Roberts 2009), so that the initial egg size is unknown. Therefore, more information on the consequences of egg size for the phenotype of individual offspring and on the persistence of the effects of egg size is required.…”
Section: Introductionmentioning
confidence: 99%
“…After feeding Dicentrachus labrax for 6 months with half of the normal feed ration, spawners growth rates were lower, and egg and larval sizes were smaller than those noted in fish fed the full ration (Cerdá, Carrillo, Zanuy & Ramos ). The restrictive feeding of Brycon amazonicus (Spix & Agassiz) resulted in smaller egg size and fewer ovulating females (Camargo & Urbinati ). On the other hand, restrictive feeding of Tilapia zillii Gervais and rainbow trout Oncorhynchus mykiss (Walbaum) (Ridelman, Hardy & Brannon ; Coward & Bromage ) has not reduced the GSI.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, we have demonstrated that protein mobilization is the primary energy source in food-deprived adult R. quelen. This is an unusual pattern, and represents a significant finding, since fish may experience limited food availability and a reduction in food intake, both in natura and in aquaculture, e.g., during pre-harvest fasting, shipping management, and feeding regimes that restrict food availability (Mackenzie et al, 1998;Souza et al, 2003;Camargo and Urbinati, 2008). Like all animals, fish need protein, fat, carbohydrates, vitamins, minerals, and other dietary elements to satisfy their physiological needs for growth and reproduction (Hertrampf and Piedad-Pascual, 2000).…”
Section: Fasting 0dmentioning
confidence: 99%
“…quelen, as with other fish species, may experience periods of food deprivation or starvation-both in natura (due to limited food availability in winter and the reduction in food intake associated with life-cycle phenomena, e.g., spawning migration) and also in aquaculture (due to pre-harvest fasting, as well as shipping management and feeding regimes, which restrict availability of food) (Mackenzie et al, 1998;Souza et al, 2003;Camargo and Urbinati, 2008). Natural or artificial fasting periods produce a number of hormonal and biochemical changes, including reduction in muscle glycogen and mobilization of fat and protein, which may impair fish meat quality (Sigholt et al, 1997;Thomas et al, 1999).…”
Section: Introductionmentioning
confidence: 99%